Groups in practice - Susan X Day (Lahaska Press, 2007)
This text provides broad coverage within a thematic framework that helps students gain insight into how groups work. In addition to balanced coverage of key groups theories and skills, the text takes a full chapter to focus on psychoeducational groups. Students will benefit from carefully constructed pedagogy that encourages them to reflect, interpret, and develop their own ideas about how groups function. The coverage of theory is made interesting through the personal insights and reflections of the author. Clear and vivid language, as well as literary references, personal disclosure, and vibrant examples help to effectively present material, promote understanding, and engage students. To further enhance the learning experience, transcripts of group interactions throughout the text provide a realistic view of a group setting. These sessions can be viewed in their entirety on the accompanying video